Functional Domain of Bovine Milk Lactoferrin Which Inhibits the Adherence of Streptococcus mutans Cells to a Salivary Film - Oho, Takahiko (American Society for Microbiology, 2002)
The bovine lactoferrin molecule and relatively long lactoferrin fragments containing residues 473 to 538 strongly inhibited adherence of Streptococcus mutans to saliva-coated hydroxyapatite beads. Each cysteine residue in Lf411 (residues 473 to 538) was replaced by a serine residue, and the mutants Lf411-C481S and Lf411-C532S strongly inhibited S. mutans adherence. These results suggest that the functional domain of lactoferrin that binds to a salivary film lies in residues 473 to 538 and that the region might be concealed by disulfide bond formation between Cys481 and Cys532 in the Lf411 fragment.